2008
DOI: 10.1111/j.1559-4572.2008.07651.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Disease in Human Immunodeficiency Virus‐Infected Children

Abstract: Cardiometabolic problems in children with human immunodeficiency virus (HIV) infection have recently begun to emerge as distinct clinical problems that require monitoring and often intervention. The cardiometabolic issues that face HIV-infected children include high rates of unfavorable lipid profiles, insulin resistance, cardiovascular inflammation, and vascular stiffness as well as the phenotypic features of truncal adiposity and facial/extremity wasting. Children differ from adults in that many have been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…However, exercise capacity is sometimes poorly correlated with cardiac function, because several other late factors can influence exercise capacity. These factors include overall deconditioning as a result of a sedentary lifestyle, psychosocial problems, depression, increased body fat, 25,335,621 mitochondrial dysfunction, chronic fatigue, other late endocrine effects, peripheral neuropathies, abnormal pulmonary function, scoliosis, and autonomic dysfunction. One recent study showed that despite subclinical cardiac dysfunction, children treated with anthracyclines (median dose, 240 mg/m 2 ) had normal physiological responses to exercise.…”
Section: Exercise Capacity and Physical Activity Interventionsmentioning
confidence: 99%
“…However, exercise capacity is sometimes poorly correlated with cardiac function, because several other late factors can influence exercise capacity. These factors include overall deconditioning as a result of a sedentary lifestyle, psychosocial problems, depression, increased body fat, 25,335,621 mitochondrial dysfunction, chronic fatigue, other late endocrine effects, peripheral neuropathies, abnormal pulmonary function, scoliosis, and autonomic dysfunction. One recent study showed that despite subclinical cardiac dysfunction, children treated with anthracyclines (median dose, 240 mg/m 2 ) had normal physiological responses to exercise.…”
Section: Exercise Capacity and Physical Activity Interventionsmentioning
confidence: 99%
“…40 HIV-infected children are at similar risk with studies showing higher rates of cardiovascular disease risk factors among HIV-infected children compared to controls. 19,41,42 Low physical functioning may either contribute to cardiovascular risk 43,44 or be a result of it. 45 In our study, HIV-infected children who had metabolic abnormalities including higher hemoglobin A 1C , triglycerides, and insulin were associated with lower VO 2 peak, although these associations did not remain significant when other factors, such as body fat and ARV exposures, were accounted for (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIV-infected individuals are at an increased risk of CVD. 2,22,30,31,42,43 Low serum 25-hydroxyvitamin D concentrations are associated with CVD risk factors in children and adults in both the HIVinfected and HIV-uninfected populations. [42][43][44][45] Furthermore, consuming the recommended amounts of potassium and sodium can help regulate blood pressure, another important factor in reducing CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…18,22,24,[26][27][28] Like HIV-infected adults, increased risk for CVD and metabolic abnormalities occur among HIV-infected youth. 18,22,[29][30][31][32] Combined with a rising prevalence of obesity in this population and higher nutritional risk due to growth and development demands, nutritional deficiencies in this population are particularly alarming. 29,33 Moreover, chronic immune activation and increased oxidative stress in HIV-infected youth may result in increased nutrient needs beyond the recommended intakes, 6,20,34 while those individuals with hyperlipidemia or metabolic dysfunction may need to decrease their total fat, trans fat, saturated fat, and cholesterol intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation